A Phonological Study of the Influence of Arabic Stress on the Pronunciation of English Words by Saudi ESL Learners - Reem Maghrabi (Journal of Arts, Literature, Humanities and Social Sciences, 2021)
Stress plays a profound role in languageintelligibility and comprehensibility. However, stress is considered a problematic area by ESL learners. Many studies have examined L2 acquisition of suprasegmmental elements such as pitch, tone and intonation, but few have focused on stress in relation to Arabic language transfer. For example, Guion(2003) has studies the influence of the factors of syllable structure and word class on stress assignment by ESL learners. Kelley (1992) has studied the influence of language stress properties on the second language acquisition of primary word stress. This paper investigates English word stresspronunciation errors by of Saudi learners of ESL. Itintends to examine the transference of Arabic on the learning of English word stress by Saudi learners of ESL.It explores the relation between language interference and stress assignmentin disyllable words(including compound words) and word-class pairs. It also examines if knowledge of noun/verb grammatical class could influence the production of stress. Moreover, it aims to explore thecorrelation between misplacement of stressand vowel change by Saudi ESL learners. Thirty three Saudi advanced learners of ESL participated in three experiments to produce 20 English disyllable words, 20 English compound words, and 20 English disyllabic word-class pairs. The errors in stress placement were inversely not proportional to the level of proficiency in English as students continued to incorrectly assign stress in disyllable words, compound words and word-class pairs. Most Saudi students placed initial stress on disyllabic words and final stress on compound words, a rule that is used with SA words. There is a correlation between stress misplacement and vowel change in disyllable words and word-class pairs but not in compound words. Errors occur more frequently with word-class pairs regardless of the students’ knowledge of grammatical class stress assignment rules.